Pupuk Cair Sabut Kelapa untuk Produksi Bougainvillea: Penyuluhan pada PKK RT 20, Kelurahan Pakuan Baru, Kota Jambi - Nasution, Hasriati; Emanauli; Yusfaneti (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
Bougainvillea is a popular type of flower in Indonesia, admired for its vibrant colors and attractive variations. Despite being widely cultivated, in-depth understanding of the adaptation and morphology of this plant remains limited. This community service initiative aims to enhance the understanding and skills of cultivating bougainvillea, particularly among the members of the PKK (Pemberdayaan Kesejahteraan Keluarga) in RT 20, Pakuan Baru, Jambi City. The primary focus is on meeting the nutritional needs of the plants by utilizing agricultural waste, such as coconut coir, as a material for organic potassium fertilizer. Typically grown to approximately 1 meter as an ornamental plant, bougainvillea's visual appeal is expected to be further enhanced through the application of liquid organic fertilizer derived from coconut coir, promoting brighter and more fertile flower displays. The outreach activities involve two stages: providing information on the production of liquid organic fertilizer from coconut coir and demonstrating its application in cultivation. The woman of the PKK group exhibited high enthusiasm and active participation in these activities. The results of the outreach indicated a solid understanding within the group. It is anticipated that this increased comprehension will motivate them to produce the appropriate dosage of liquid organic fertilizer from coconut coir, optimizing the growth of bougainvillea or paper flowers, resulting in the flourishing of beautiful and abundant blooms.